The Effect of Speaking Anxiety on EFL Saudi Learners’ Performance - AbuSahyon, Alia Sa’ad Eldin; Almukhales, Retaj Ali; Makhashen, Shatha Saeed; AlHarthi, Renad Ebraheem (International Journal of Membrane Science and Technology, 2023)
Anxiety plays a significant role in students’ oral performance and achievement in EFL speaking classes. This study applied a mixed-method approach using a questionnaire and semi-structured interviews in order to investigate tertiary level students’ English language anxiety at Najran University. It also examines its main causes. In addition, it explores the effects of anxiety on students’ performance in EFL classrooms and the role of gender differences on the level anxiety. The study reveals that the main factors that contribute to EFL speaking anxiety among Saudi EFL students are fear of negative evaluation, fear of interaction, fear of perception of others and lack of confidence, respectively. The study also found that female students were more anxious compared to male students in EFL speaking classrooms. In addition, it showed a negative connection between FLA and students’ performance in speaking classes in that high-level anxiety students experience poor speaking performance. The study implicates the role of speaking teachers in reducing the anxiety among students.